2017
DOI: 10.1186/s12888-017-1258-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telephone follow-up on repeated suicide attempt in patients discharged from an emergency psychiatry department: a controlled study

Abstract: BackgroundAttempted suicide is a major public health problem, and the efficacies of current postvention protocols vary. We evaluated the effectiveness of telephone follow-up of patients referred to an emergency psychiatric unit for attempted suicide on any further attempt/s over the following year.MethodIn a single-center, controlled study with intent to treat, we evaluated the efficacy of a protocol of telephone follow-up of 436 patients at 8, 30, and 60 days after they were treated for attempted suicide. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
0
41
1
1
Order By: Relevance
“…Discharge from acute mental health services is often described as a dangerous, chaotic, and emotionally driven time-period for patients (1). This time period has long been associated with mortality, risk, and related adverse outcomes for patients (2)(3)(4)(5). In England, between 2006 and 2016, there were 2,220 suicides within 3 months of discharge from inpatient mental health care (2).…”
Section: Introductionmentioning
confidence: 99%
“…Discharge from acute mental health services is often described as a dangerous, chaotic, and emotionally driven time-period for patients (1). This time period has long been associated with mortality, risk, and related adverse outcomes for patients (2)(3)(4)(5). In England, between 2006 and 2016, there were 2,220 suicides within 3 months of discharge from inpatient mental health care (2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides taking an individual's history of attempted suicide as the warning signs and risk factors for suicide as the English guidelines did, it is needed to include additional actions specifically used to address issues related to repeated suicidal attempts among Chinese people (e.g. to detect long-lasting relationship conflicts, ongoing mental health problems, or inappropriate problem-solving strategy), in order to prevent subsequent attempts and the risk of death from suicide [39].…”
Section: Repeated Suicidal Attemptsmentioning
confidence: 99%
“…Of the studies that aimed to reduce suicide, one found letters to recently discharged service users ineffective [6]. Whilst the other found only very early telephone follow-ups to be effective in a large-scale randomised controlled trial [5]. A small-scale RCT found intensive case management (weekly face-to-face contact and suicidal ideation and suicidal ideation and increased service contact, satisfaction and better relationships with professionals [34].…”
Section: Contact-based Interventionsmentioning
confidence: 99%
“…Only three studies in the review focused on reducing suicide post-discharge [5,6,34]. In the unsuccessful intervention 8 letters were sent to service users in the year after discharge, but this had no effect on suicide [6].…”
Section: Reducing Suicidementioning
confidence: 99%
See 1 more Smart Citation